Energy management practices and implementation in campus building - Nidzamuddeen, Ishak (2016)
Energy management and efficiency in building have attracted lots of attention in recent years. Various findings, products and systems in energy management and efficiency aspect have been produced in order to support the needs for a better and greener environment. New wave of energy management and efficiency programs nowadays not only just merely a product installation or specific system solution, but offer a wider approach like the management system, finding baseline energy use, benchmarking, and then only to provide reasonable return-on-investment solution. Therefore, a proper and right model of implementation should be carefully designed before implementing any energy saving measures in order to get a valid and optimized result. Thus, this research proposed a new model of energy management and efficiency system with the specific target of implementation in university campus. An energy management model is developed and findings of energy saving measures from the proposed model will be discussed. A test-bed model is also being developed in order to simulate the real energy management and efficiency in campus. Based on the energy management model and the test-bed proposed, a better result and method of energy saving implementation in campus building is obtained and proved. Finding, result and solutions based on the new model is also being discussed as to put a clear picture on the sustainable energy management purposes in campus building.